Arbuscular mycorrhizal interactions of mycoheterotrophic Thismia are more specialized than in autotrophic plants - Gomes,SIF; Aguirre-Gutierrez,J; Bidartondo,MI; Merckx,VSFT (New Phytologist, 2016)
In general, plants and arbuscular mycorrhizal (AM) fungi exchange photosynthetically fixed carbon for soil nutrients, but occasionally nonphotosynthetic plants obtain carbon from AM fungi. The interactions of these mycoheterotrophic plants with AM fungi are suggested to be more specialized than those of green plants, although direct comparisons are lacking.We investigated the mycorrhizal interactions of both green and mycoheterotrophic plants. We used next-generation DNA sequencing to compare the AM communities from roots of five closely related mycoheterotrophic species of Thismia (Thismiaceae), roots of surrounding green plants, and soil, sampled over the entire temperate distribution of Thismia in Australia and New Zealand.We observed that the fungal communities of mycoheterotrophic and green plants are phylogenetically more similar within than between these groups of plants, suggesting a specific association pattern according to plant trophic mode. Moreover, mycoheterotrophic plants follow a more restricted association with their fungal partners in terms of phylogenetic diversity when compared with green plants, targeting more clustered lineages of fungi, independent of geographic origin.Our findings demonstrate that these mycoheterotrophic plants target more narrow lineages of fungi than green plants, despite the larger fungal pool available in the soil, and thus they are more specialized towards mycorrhizal fungi than autotrophic plants.